Peran Sistem Boarding School dalam Meningkatkan Kemandirian Siswa MTs Negeri 1 Temanggung - Fairuzza Arza Zariroh; Sri Haryanto; Muhammad Saefullah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the activities within the boarding school system and the forms of student independence at MTs Negeri 1 Temanggung. This research is classified as field research with a descriptive qualitative approach. The data were obtained through interviews with two dormitory supervisors and ten boarding school students, as well as observations related to teacher instruction and student independence. The results of this study indicate that the boarding school system at MTs Negeri 1 Temanggung is effective in enhancing students' independence. This is achieved through a structured and disciplined dormitory life that integrates academic, religious, and daily life activities aimed at fostering self-reliance. Students are trained to manage their time, take care of their personal needs, and take responsibility in collective activities. A key supporting factor in the boarding school system's success in promoting student independence is its well-structured management. However, a major inhibiting factor in optimizing the role of the boarding school system in enhancing student independence at MTs Negeri 1 Temanggung is the limited number of dormitory supervisors.